An overview on advances in computational fracture mechanics of rock. Issue 4 (4th July 2021) - Mohammadnejad, Mojtaba; Liu, Hongyuan; Chan, Andrew; Dehkhoda, Sevda; Fukuda, Daisuke
Abstract: Due to its complexities, rock fracturing process still poses many pressing challenges despite intense research efforts. With the rapid development of computational mechanics, numerical techniques have gradually become robust tools for the investigation of rock fracture. Nevertheless, not all of the devised methods are capable of adequately modelling the rock fracture process. For an accurate simulation of the process, a numerical method needs to be capable of modelling crack initiation, propagation, bifurcation, coalescence and separation. This paper provided a review of recent advances in computational analysis of the rock fracture process, which is built upon a number of literature on numerical modelling of mechanics of failure in rock and other brittle materials. After briefly discussing the fundamentals of rock fracture mechanisms, the basic structure of the existing and recently developed numerical techniques such as finite element method, boundary element method, distinct element method, combined methods and multi-scale coupled method are illustrated. Finally, the strengths and weaknesses of these numerical techniques are discussed and the most promising methods are highlighted.